THE INFLUENCE OF EDUCATIONAL INNOVATIONS ON THE CREATIVE DEVELOPMENT OF FUTURE TEACHERS OF MUSIC - Сивак, В.О.; Сивак, Т.Г. (Modern engineering and innovative technologies, 2023)
The article substantiates the essence of educational innovation as a separate field of scientific knowledge. Modern requirements for the professional training of future music teachers in the context of the development of creative professional abilities ar